Shear Wave Elastography of the Sciatic Nerve and Its Relationship with Posterior Chain Flexibility in Healthy Participants: An Observational Study - Charles Cotteret; Jaime Almazán-Polo; Ángel González-de-la-Flor (Sensors)
Introduction: Shear wave elastography (SWE) has been widely used to assess the mechanical properties of peripheral nerves, including the sciatic nerve. However, the relationship between sciatic nerve stiffness and posterior chain flexibility remains unclear. Therefore, we aimed to examine differences in sciatic nerve stiffness and shear wave speed (SWS) based on limb dominance and hamstring flexibility, and to explore their association with posterior chain mobility assessed through AKE and ASLR tests in healthy individuals. Methods: An observational study was conducted on 25 healthy, physically active participants (49 lower limbs). Sciatic nerve stiffness was measured using SWE at a standardized location in the posterior thigh. Posterior chain flexibility was assessed using the Active Knee Extension (AKE) and Active Straight Leg Raise (ASLR) tests. Participants were categorized based on hamstring flexibility, and comparisons were made between dominant and non-dominant limbs. Results: Participants with limited hamstring flexibility exhibited significantly higher AKE and ASLR values (p < 0.001) and showed an increased stiffness and SWS towards greater sciatic nerve (p = 0.05), although correlations between SWE values and flexibility tests were not significant. No significant differences were found between dominant and non-dominant limbs in AKE (p = 0.28), ASLR (p = 0.47), SWE (p = 0.38), or SWS (p = 0.34) values. Conclusions: Although no significant correlations were found between SWE parameters and flexibility tests, individuals with limited posterior chain mobility exhibited higher sciatic nerve stiffness in healthy participants.